Compartment temperature estimation of a multiple-layer cable tray fire with different cable arrangements in a closed compartment. (July 2019) - Huang, Xianjia; Wang, Yuhong; Zeng, Wuyong; Peng, Lan; Cheng, Anthony CH; Chow, WK
Fire hazard analysis of multiple-layer cable tray is an important part of nuclear safety analysis. Large-scale cable fire experiments with a three-layer horizontal cable tray were conducted in a closed compartment. The vertical temperature profile in the middle of the room was acquired. Distinctive stratification phenomena were found in the vertical temperature distribution. The interface between the upper and lower layer was located at approximately the height of the top cable layer. Heat transfer between the smoke and compartment walls occurred mainly above the smoke interface. A modified non-steady energy balance model in a closed compartment which included the effect of smoke interface height was used to estimate the compartment temperatures. Compared with the experimental results, the modified model for the multiple-layer cable tray fire in a closed compartment provides better estimation than the original model.